Aplikasi Larutan Hara dan Zat Pengatur Tumbuh terhadap Pertumbuhan Tanaman Pakcoy dengan Sistem Hidroponik - Sinaga, Reflianta Br; Ginting, Nelva Meyriani; Budiman, Indra; Lase, Agustinus (Jurnal Kridatama Sains dan Teknologi, 2024)
Pakcoy is a type of plant that belongs to the mustard family with the Latin name Brassica rapa L. Pakcoy plants can be cultivated with hydroponic technique, which is a plant cultivation technique without soil media. Hydroponics is one of the solutions in overcoming the limited land in urban areas. This study aims to analyze the effect of nutrient solution concentration and the provision of growth regulators on the growth and production of pakcoy plants using the hydroponic method. The research was conducted in a completely randomized design (CRD) involving two factors. The first factor was the concentration of nutrient solution (N) with two levels: N1 = 700 ppm, 900 ppm, and N2 = 1,000 ppm, 1,200 ppm. The second factor is growth regulator (H) consisting of five levels: H0 = Control (no hormone), H1 = 1 ml/l water, H2 = 2 ml/l water, H3 = 3 ml/l water, and H4 = 4 ml/l water. Parameters observed included plant height, number of leaves, and wet weight. The results showed that the concentration of nutrient solution had a significant effect on the number of leaves and wet weight, but not significant on plant height. Meanwhile, the application of growth regulators also had a significant impact on the number of leaves and wet weight, but had no significant effect on pakcoy plant height. In general, increasing the concentration of nutrient solution and dosage of growth regulators increased the growth of pakcoy plants